Fokalisasi dalam Cerpen Unsu Joeun Nal karya Hyeon Jin Geon - Fitri, Humaira Achirul (East Asian Review, 2023)
This study discusses the form of focalization used in the short story titled Unsu Joeun Nal written by Hyeon Jin Geon. This study aims to identify and analyze the form of focalization used in the short story Unsu Joeun Nal. The data for this study are parts of the text in the short story Unsu Joeun Nal which are considered to show the form of focalization. To achieve the research objectives, this research utilizes Genette (1980) focalization theory as an approach to conduct the research. The analysis results of the focalization forms in the short story Unsu Joeun Nal resulted in the finding that Unsu Joeun Nal showed characteristics of zero focalization and internal focalization form, while the characteristics of external focalization form could not be found. The result also show that the utilization of zero focalization form is more dominant in the storytelling of the short story Unsu Joeun Nal. This is shown through the presence of the narrator who shows all the narrator's characteristics in the form of zero focalization. The utilization of zero focalization has a role in making the reader understand the story conveyed through the various elements in it.